Principles and criteria of speech flow phonological segmentation: Controversial aspects - M.B. Popov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2017)
The paper discusses the criteria for segmentation into phones, which is one of the procedures for establishing the phoneme inventory in a given language. For the most part it is a matter of the St. Petersburg School of Phonology (Shcherba School). For the Shcherba School, it is the constituent (not distinctive) function of the phoneme that is the most important. Accordingly, the segmentation into phones should rely on the semantic level of language, i.e., on morphemic boundaries: if in a given language a morphemic boundary is possible inside an ambiguous sound segment, this segment must be a realization of two phonemes. English monophonemic diphthongs and Russian biphonemic and monophonemic diphthongs demonstrate the effectiveness of this criterion, as well as a prevocalic glottal stop, which is not a phoneme in Russian, being rather a part of the next vowel, because it is never separated from the next vowel by morphemic boundary. Application of the criteria of morphological alternations and so called “residual discriminability” has been criticized. One can relate the use of these criteria at the stage of phonological segmentation to unclear discrimination of the notions “syntagmatic identification”, “autonomy” and “reality” of phoneme as a linguistic unit. The hypothesis has been put forward in the paper that the notion of “residual discriminability” is the product of erroneous interpretation of L.V. Shcherba's statement, which says not about the criteria of phonological segmentation, but about autonomy of phoneme with regard to morpheme.